Pemanfaatan Palm Oil Fuel Ash (Pofa) Sebagai Bahan Stabilisasi Tanah Gambut - Alicia Silva Indah Putri Dinata; Dila Oktarise Dwina; Heriansyah Putra (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
Peat soil is characterized by high moisture and organic matter contents, resulting in low bearing capacity and making it unsuitable as a subgrade material for road construction. One promising approach to improve its engineering properties is stabilization using Palm Oil Fuel Ash (POFA). This study aimed to review the potential of POFA and carrageenan in improving the bearing capacity of peat soil based on the California Bearing Ratio (CBR). A literature review approach was employed by collecting and analyzing scientific journal articles, conference proceedings, books, and technical standards related to peat soil characteristics, the use of POFA as a pozzolanic material, and CBR performance of stabilized peat soil. The review indicates that POFA functions as both a filler material and a silica source that promotes pozzolanic reactions, leading to improved soil density and strength. Utilization of POFA has the potential to increase CBR values, reduce moisture content and swelling, and improve the microstructure of peat soil. Based on the findings of previous studies, POFA and carrageenan are considered promising environmentally friendly and sustainable stabilization materials for peat soil. However, further experimental investigations are still required to determine the optimum mixture proportion capable of providing the highest improvement in bearing capacity.